A Form of Choreography Padendang Dance in Bugis Community in Soppeng Regency - Yusrianti Yusrianti; Hartati Hartati; Damayanti Damayanti; sam hermansyah sam hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
Padendang Dance is a series of traditional Mappadendang ceremonies, which have the characteristics of movement, costumes and property. So that the uniqueness can be seen from the form of padendang dance choreography. This research aims: (1) Reviewing the Origins of Padendang Dance in Bugis Community in Soppeng Regency (2) Reviewing the form of Padendang dance choreography in the Bugis community in Soppeng Regency. This research uses a qualitative research approach with phenomenological design. The research site in Abbanuangnge Village of Soppeng Regency. Data collection techniques with observation techniques, interviews and document studies. Data analysis techniques from Jannet adshead start from discribing, discerning, interpreting, dan evaluating. The first research results, the origin of padendang dance and the second form of choreography of Padendang dance consisting of three parts, the beginning, the core and the final part. The beginning includes the variety of motion mappakaraja and sere describe respect and request permission to the audience / community. The core part includes motion maggalattungeng (dancer attractions), mengampo bine, mattaneng, masssangki, Which describes the activities of the farming community. The final part Mappatabe’ request permission and apologies to the community if there is a mistake in the performance of Padendang dance. The message conveyed remains grateful and maintains a sense of togetherness and the appearance in question is the implementation of padendang dance at night supported by moonlight and the place of implementation that is laid out carpet and decorated with yellow janur. The advice that can be conveyed is that the community continues to preserve Padendang dance and increase public interest / appreciation of Padendang dance. By maintaining keorisinal without reducing the variety of Padendang dance movements so that the depiction of Padendang dance message can be conveyed. There is a need for coaching in schools to attract young people who have the potential in developing Padendang dance.